EVALUASI DAN PENETAPAN LAHAN PERTANIAN BERKELANJUTAN UNTUK PENCEGAHAN ALIH FUNGSI LAHAN DI KABUPATEN BANGLI - Adnyana, I Made; Puja, I Nyoman; Arthagama, I Dewa Made (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 11 No 1 (2017), 2017)
EVALUATION AND DETERMINATION OF SUSTAINABLE LAND AGRICULTURE FOR PREVENTION OF LAND CONVERSION IN BANGLI REGENCY The research was done in the area of ??paddy soil in  Bangli District, Bangli Regency  to identification, evaluation, and mapping the paddy soil area that have to maintain as a sustainable agriculture. To achieve these objectives, the research conducted through several activities, namely: soil survey and environment, physical and chemistry of soil analysis, and   mapping the model of the prevented exchangeable paddy soil functions. Depend on plan lay out space (called RTRW) of Bangli regency, there were two models of sustainable agriculture decision at district of Bangli, where in each model, land (Subak) mapping as subak everlasting, subak buffer, and Subak convertion. Subak convertion was have opportunity to changing function. Subak convertion of Model I as 158,68 ha (2011 – 2021) and Model II as 78,14 ha (2021 – 2031) respectively.